Velocity-free spacecraft attitude stabilization using two control torques. (November 2019) - Frias, Alexander; de Ruiter, Anton H.J.; Kumar, Krishna Dev
Abstract: The attitude stabilization of an inertial-pointing underactuated rigid-body spacecraft using two torques under time-varying disturbances and inertia matrix uncertainties is examined. An observer-based time-varying output feedback control law is proposed where angular velocity measurements are not available. The stability of the combined controller–observer system is proven rigorously to show local ultimate boundedness of all states. A comprehensive numerical example is presented with sampled-data implementation of the observer-based control law to demonstrate convergence even with very large initial attitude errors.